Production Challenges in Small and New Poultry Farms in Northern Jordan - Abudaieh, Ahmad; Binti Omar, Khatijah; Bin Samsudin, Hazman; Abi Sofian Abdual Halim, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to understand and measure the problems of production of small and new poultry farms in northern Jordan. The sample was of 150 farms that were under 3 years of age (working since three years or less) and with less than 2k livestock. A simple frequency analysis was conducted on the three sections of the questionnaire used in this research, and the results show that problems of high cost of production (high cost of feed, high cost of young birds) were the most frequent causes of production problems. The results also show a high rate of debt among farmers and low profitability because of low product prices in the market. The majority of farmers were ready to sell the farms if they got a suitable offer. These problems are the same as problems from 10 years ago in this sector, which show no solutions were done in these years for this sector.